Public enterprises survey 1985-86 [vol.3 pt.1] annual report on the working of industrial and commercial undertakings of the central government - India.Ministry of Industry. Bureau of Public Enterprises (Bureau of Public Enterprises, Ministry of Industry, Govt. of India New Delhi, 1984)
|
Keywords: Enterprises performance report -- 1986-87 -- India -- Public enterprises survey 1986-87 -- India; Enterprises producing & selling -- 1986-87 -- India